2019
DOI: 10.1007/jhep11(2019)026
|View full text |Cite
|
Sign up to set email alerts
|

Pion condensation in a soft-wall AdS/QCD model

Abstract: Finite isospin chemical potential µ I and temperature T have been introduced in the framework of soft-wall AdS/QCD model. By self-consistently solve the equation of motion, we obtain the phase boundary of pion condensation phase, across which the system undergoes a phase transition between pion condensation phase and normal phase. Comparing the free energy of solutions with and without pion condensation, we find that the phase transition is of first order type both at large µ I and small µ I . Qualitatively, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 144 publications
(277 reference statements)
1
11
0
Order By: Relevance
“…In this paper, we have studied pion condensation and chiral condensation with finite µ I and finite T in the IR improved soft-wall AdS/QCD model. Under a fixed T f , we find that pion condensation exists two critical points separately located in small µ I region and large µ I region, similar behaviors also show in the LQCD in Ref [38], the NJL model in Ref [17] and a solf-wall model in Ref [77]. The behaviors of the pion condensation continuous changes from zero to non-zero and the measured values of critical exponent β are very close to 1/2, which indicates the pion condensation is of second order and belong to 4D mean field class.…”
Section: Conclusion and Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In this paper, we have studied pion condensation and chiral condensation with finite µ I and finite T in the IR improved soft-wall AdS/QCD model. Under a fixed T f , we find that pion condensation exists two critical points separately located in small µ I region and large µ I region, similar behaviors also show in the LQCD in Ref [38], the NJL model in Ref [17] and a solf-wall model in Ref [77]. The behaviors of the pion condensation continuous changes from zero to non-zero and the measured values of critical exponent β are very close to 1/2, which indicates the pion condensation is of second order and belong to 4D mean field class.…”
Section: Conclusion and Discussionsupporting
confidence: 79%
“…It has been shown that the phase transition, between normal phase and pion condensation phase, is of second-order with mean-field critical exponents and happens at µ c I = m 0 . Efforts have also been made in the soft-wall framework at finite temperature [77]. It shows that the phase transition is of first-order with two both left and right critical µ I at a particular temperature, which are quite different from the hard wall results.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The results from these first simulations were in qualitative agreement with the different approaches to QCD . Other interesting approach that is applied to study QCD at finite isospin chemical potential is based in holographic models [62][63][64][65][66][67][68]. More recently, lattice QCD results for finite isospin density were performed using an improved lattice action with staggered fermions at physical quark and pion masses [69][70][71][72], their predictions being in very good agreement with the results obtained from updated chiral perturbation theory [73][74][75] and NJL models [76][77][78].…”
Section: Introductionmentioning
confidence: 81%
“…Given the nonperturbative character of QCD at the energy scales of the various phase transitions in Figure 1, the Lagrangian in Equation (2) is of little direct use. Various theoretical approaches have been developed, including linear sigma models and chiral perturbation theory (χPT) [10,11,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], the Nambu-Jona Lasinio (NJL) models , the quark-meson models [57][58][59][60][61][62], the random matrix model [63,64], the AdS/QCD model [65] and perturbative QCD (pQCD) (with diagrams resummation) [66,67]. A guiding role in this forest of theoretical approaches is played by the lattice QCD (LQCD) simulations [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82], which provide a powerful ...…”
Section: Outside the Beta-equilibrated Sheetmentioning
confidence: 99%